Efforts To Combine High-Politics And Low-Politics: How Muhammadiyah Special Region of Yogyakarta Wins Its Cadres as Members of the Regional Representative Council of the Republic of Indonesia - Suswanta, Suswanta; Sutan, Arissy Jorgi (Al-Risalah, 2024)
The purpose of this article is to explain Muhammadiyah's personal branding strategy for the Special Region of Yogyakarta in winning its cadre, Ahmad Syauqi Soeratno, to become a member of the Regional Representative Council of the Republic of Indonesia in the 2024 election. Ahmad Syauqi Soeratno won 398,903 votes or 17.32% of the total percentage through this strategy. This political, institutional support is interesting to explain because it shows the practice of low politics, even though Muhammadiyah's political doctrine has been to play a role in high politics or national politics and not low politics, which is power-oriented. This article is the result of qualitative research, which uses interview techniques, observation, documentation, Focus Group Discussion, and Nvivo 12 Plus and Geographic Information System in its analysis. The discussion results show that the personal branding carried out by the Yogyakarta Special Region Muhammadiyah towards Ahmad Syauqi Soeratno can be understood as an effort to combine high politics and low politics in seizing power and policy space. The separation of high and low politics is not rigid in its implementation at the local level. This political flexibility does not mean opportunism because it remains within the framework of preaching reform or tajdid in the political field. To realize the interests of political da'wah, the electoral behavior of Muhammadiyah citizens is more effectively controlled institutionally so that the potential of the Muhammadiyah network can be optimized rather than given the freedom to choose.